2011
DOI: 10.1136/emj.2010.104380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triage methods used to select patients with suspected pandemic influenza for hospital admission

Abstract: Although limited by a paucity of cases, this research shows that current triage methods for suspected pandemic influenza did not reliably discriminate between patients with good and poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A recent systematic review on prediction models for diagnosis and prognosis of COVID-19 reported that proposed models were poorly described, had a high risk of bias, and may be unreliable when used in situ [109]. Most triage protocols were developed with experts (e.g., ethicists, lawyers, healthcare professionals, decision-makers and, in some cases, members of the public) in advance of a pandemic (e.g., CHES T consensus statements) [11,88,91,96,100,110] or were validated using a non-representative population (e.g., patients with COVID-19, seasonal influenza or ARDS) [111][112][113][114][115][116][117][118][119]. As such, most triage criteria are not validated (and it may not be possible to validate them) prior to their use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on prediction models for diagnosis and prognosis of COVID-19 reported that proposed models were poorly described, had a high risk of bias, and may be unreliable when used in situ [109]. Most triage protocols were developed with experts (e.g., ethicists, lawyers, healthcare professionals, decision-makers and, in some cases, members of the public) in advance of a pandemic (e.g., CHES T consensus statements) [11,88,91,96,100,110] or were validated using a non-representative population (e.g., patients with COVID-19, seasonal influenza or ARDS) [111][112][113][114][115][116][117][118][119]. As such, most triage criteria are not validated (and it may not be possible to validate them) prior to their use.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Hlavinkova et al14 reported that cardiovascular diseases, DM, and bronchial asthma are significant predictors of hospital admission. Additionally, patients with high CURB-65 scores were likely to be admitted according to Challen et al15…”
Section: Discussionmentioning
confidence: 99%
“…ILI, according to the Centers for Disease Control and Prevention (CDC), was defined as a history of fever or sudden onset of fever (>37.8°C, within 7 days) and a cough and/or sore throat without a known acute respiratory infection other than influenza. The following SARI case definition was used: (1) history of fever or sudden onset of fever (>37.8°C, within 7 days), (2) one or more respiratory symptom (cough, sore throat, rhinorrhea), (3) shortness of breath or difficulty breathing, and (4) admission [11]. However, the HIMM system uses “modified SARI,” which is defined as either (A) classical SARI by WHO or (B) non-ILI SARI with laboratory-confirmed influenza-related admission.…”
Section: Methodsmentioning
confidence: 99%